Examining the relationship between flexible working arrangements and employee performance: a mini review - Çivilidağ, Aydın; Durmaz, Şerife (Frontiers in Psychology, 2024)
This research aims to determine the relationship between flexible working arrangements (FWAs) and employee performance (EP). The research was conducted by reviewing studies in Web of Science (WoS), EBSCO and Google Scholar databases between 2010 and 2024. The research was screened in the databases in line with the inclusion criteria, which were determined as studies written in English, where data were collected by survey technique, data were analyzed by correlation, and those that met the criteria were included in the research. As a result of the preliminary screening, second screening, and screening in line with the inclusion criteria, the remaining 21 studies constituted the data set of this study. The correlation between FWAs and EP was (r(20)=0.596, p<.05). This value can be interpreted a significant and high-level relationship between them. According to the random model, Fisher's Z and 95% CI (LL=0.52 and UL=0.84), Z=8.45, measured an effect size of 0.35 p=.000. This value shows a moderate effect size according to Cohen's d. FWAs have a positive effect on EP, productivity, job satisfaction, job stress, work-family harmony, and organizational commitment. It is recommended that organizations, managers, organizational psychology, and human resources professionals (HRP) should include FWAs in job analysis, job design, and planning.